The Effect of Digital Marketing Training on the Digital Online Garage Sale Community and their Implications on Capital Investment Decisions - Didi Tarmidi; Abdul Wafiq (Enrichment : Journal of Management, 2022)
This study aims to determine the effect of digital marketing training on the online digital Garage Sale community and its implications for capital investment decisions, a case study on the West Java Kadin fostered business in Bandung. The research method applied is in the form of a descriptive analytical survey method, while the sample used is 32 respondents. The variables studied from each respondent are digital marketing training, the Digital Online Garage Sale community, and capital investment decisions. The type of data collected is primary data. The results showed that digital marketing training had an effect on the Digital Online Garage Sale community. And the Digital Online Garage Sale community influences capital investment decisions. The object of this research is the sample of respondents used is still limited to the business assisted by the West Java Chamber of Commerce in Bandung, therefore further research needs to be carried out based on more varied sampling with a longer duration, so that generalizable results are obtained.